The influence of growth hormone on pediatric body composition: A systematic review - Ferruzzi, Alessandro; Vrech, Massimiliano; Pietrobelli, Angelo; Cavarzere, Paolo; Zerman, Nicoletta; Guzzo, Alessandra; Flodmark, Carl-Erik; Piacentini, Giorgio; Antoniazzi, Franco (Frontiers in Endocrinology, 2023)
Background: Growth hormone (GH) affects metabolism and regulates growth in childhood. The most prominent feature of GH deficiency (GHD) in children is diminished height velocity that eventually leads to short stature. In adult-onset GHD, lean body mass (LBM) is reduced, and visceral fat mass (FM) increased. Beneficial effects of GH treatment on body composition in adults with GHD, including an increase in muscle mass and a decrease in FM, are well established. Relatively few studies have investigated the effects of GH treatment on the body composition of pediatric patients with idiopathic or hypothalamic-pituitary disease-associated GH deficiency. This systematic review aimed to summarize available evidence relating to the effects of GH treatment on body composition in children with GHD. Methods: The PubMed, Science Direct, Cochrane Trials, and Embase databases, were searched with keywords including “GH”, “body composition”, “children”, and “growth hormone” for English-language articles, published between January 1999 and March 2021. Two reviewers independently evaluated the search results and identified studies for inclusion based on the following criteria: participants had a confirmed diagnosis of GHD (as defined in each study); participants were pediatric patients who were receiving GH or had stopped GH treatment, regardless of whether they were pre- or post-pubertal; the intervention was recombinant human GH (rhGH; somatropin); and outcomes included changes in body composition during or after stopping GH therapy. Data extracted from each study included study quality, study sample characteristics, study interventions, and body composition. Data on fat-free mass and LBM were combined into a single category of LBM. Results: Sixteen studies reporting changes in body composition (i.e., FM and LBM) associated with GH treatment in children with GHD were identified and included in the review. Collectively, these studies demonstrated that FM decreased, and LBM increased in response to GH replacement therapy. Conclusion: Despite study limitations (i.e., potential effects of diet and physical activity were not considered), we concluded that a periodic body composition assessment is required to ensure that a satisfactory body composition is achieved during GH replacement therapy in children with GHD.